Cardiovascular and Inflammatory Biomarkers for Defining the Prognosis of CAP: Focus on Proadrenomedullin. Issue 3 (May 2015) - Bello, Salvador; Vilá, Manel; Torres, Antoni
Abstract : Different tools have been developed to evaluate the severity of community-acquired pneumonia (CAP), to assist in making the right decisions regarding early diagnosis and treatment, and to choose the most appropriate setting for each patient. Severity scores, mainly Pneumonia Severity Index and CURB65, are widely used and have shown their clinical utility in identifying patients with a low risk of a 30-day mortality and who can be safely treated as outpatients, thus improving the choice of site of treatment and speeding up discharges. The 9 minor criteria of the ATS/IDSA score are better than both the Pneumonia Severity Index and CURB65 at identifying patients who require intensive care unit (ICU) admission. However, some key prognostic aspects closely associated with CAP morbidity and mortality, such as clinical deterioration, exacerbation of preexisting comorbidities, cardiovascular events, treatment failure, and complications, are not satisfactorily predictable with these severity scores. Several biomarkers have been tested for their ability to identify severe CAP and to choose the best site of treatment. Inflammatory biomarkers, particularly C-reactive protein (CRP) and procalcitonin (PCT), evaluate the inflammatory response, which has been associated with mortality and severity of CAP. They have proven to be of use in providing additional information to clinical severity scores and in monitoring therapy response, complications, treatment failure, death, and general outcome of CAP. However, both biomarkers used in isolation in clinical practice have considerable limitations, particularly their poor ability to discriminate high-risk patients. Because of the major role of sepsis and cardiovascular events as causes of altered outcomes in CAP, several cardiovascular biomarkers have also been tested. Proadrenomedullin (proADM) has been shown to be a better prognostic tool than inflammatory biomarkers, as it can predict short-term and long-term mortality, severity, and complications. ProADM has demonstrated a strong ability to identify low-risk patients, and its addition to clinical risk scores significantly improves their predictive power. These associations show promise in facilitating better site-of-care decisions and earlier and safer discharge in CAP. Less information is available on the ability of proADM to identify patients at risk of deterioration. Interventional studies are needed to determine its real usefulness in clinical practice.